2011
DOI: 10.1159/000324032
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration in Suspected Inflammatory Breast Cancer: Case Series with Emphasis on Approach to Specimen Adequacy

Abstract: Objectives: To highlight the utility of a tangential approach in the fine-needle aspiration (FNA) technique for obtaining cellular material adequate for a conclusive diagnosis in diffusely enlarged breast without a discrete lump. Study Design: FNA was performed on 5 women clinically suspected to have inflammatory breast cancer (IBC). All had unilateral diffusely enlarged breasts with peau d’orange changes of the skin. No distinct lump was palpable. The procedure was performed using a 10 cm3 syringe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In Kenya, where breast cancer is the most prevalent malignancy afflicting females, the vast majority of patients present with locally advanced disease detectable by palpation at physical examination . Little is published on the utility of FNAC for palpable breast lesions in Kenya, a low income country that lacks routine screening programmes and universal access to healthcare . We set out to retrospectively examine the African Inland Church (AIC) Kijabe Hospital experience with breast FNAC over an 18‐year 9‐month period of clinical practice serving as the primary referral centre for four smaller AIC hospitals and over 50 rural clinics…”
Section: Introductionsupporting
confidence: 60%
“…In Kenya, where breast cancer is the most prevalent malignancy afflicting females, the vast majority of patients present with locally advanced disease detectable by palpation at physical examination . Little is published on the utility of FNAC for palpable breast lesions in Kenya, a low income country that lacks routine screening programmes and universal access to healthcare . We set out to retrospectively examine the African Inland Church (AIC) Kijabe Hospital experience with breast FNAC over an 18‐year 9‐month period of clinical practice serving as the primary referral centre for four smaller AIC hospitals and over 50 rural clinics…”
Section: Introductionsupporting
confidence: 60%
“…The presence of lymphovascular tumor emboli in the skin biopsy and invasive mammary carcinoma in the core biopsy can establish the diagnosis and initiate the clinical management of the patients. Tissue sampling can be a particularly problematic issue in IBC, since most cases present with no discrete mass and therefore accurate targeting of the area of breast for image-guided CNBs can be difficult [ 5 , 6 ]. Shah and colleagues showed that sampling error can lead to inadequate CNB specimens, which have an insufficient amount of tissue to make a diagnosis, in as many as 9.1 % of cases [ 7 ].…”
Section: Introductionmentioning
confidence: 99%